THE RELATIONSHIP OF KNOWLEDGE OF BREASTFEEDING MOTHERS TO THE PROVISION OF COMPLEMENTARY FOOD TO BABIES TOO EARLY IN PIDOLI LOMBANG VILLAGE, SUB-DISTRICTMANDAILING NATAL DISTRICT PANYABUNGAN 2023 - DEWI SRI RAHAYU TINENDUNG (LP2MTBM MAKARIOZ, 2023)
Breastfeeding is one of the most effective ways to ensure the health and survival of the child. However, almost two days three babies are not breastfed exclusively during the recommended six months. Breast milk (breast milk) is an ideal food for babies. Improper feeding of complementary breast milk (MP-ASI) continues to drive efforts to increase the rate and duration of breastfeeding worldwide. This study aims to determine the Relationship of Breastfeeding Mothers' Knowledge to Breastfeeding Babies Too Early in Pidoli Lombang Village, Panyabungan District, Mandailing Natal Regency, 2023. The type of research used is descriptive research with a cross sectional approach The population in the study was mothers who had babies 0-5 months in Pidoli Lombang Village. The sampling technique uses Random Sampling with a large sample of 45 people. Data collection by using primary and secondary data. Data analysis using the chi -square test with a significant level of p<0.05). The results of the analysis showed that there was a relationship between the knowledge of breastfeeding mothers to the administration of complementary food in infants too early with a value of P = 0.002 where P = <0.05. It is hoped that health workers will provide information to increase maternal knowledge, through counseling at Posyandu and the community environment for mothers who do not visit Posyandu. Make information in the form of brochures about the benefits of exclusive breastfeeding and the right time to provide complementary foods that aim to increase mothers' knowledge about complementary foods and can change the mother's attitude towards a more positive direction.